Sources for the history of Ilocos in the Philippine National Archives - Foronda, Jr., Marcelino A. (1976)
Philippine local history has not merited the attention not to say the dedication of the more notable Philippine historians, relegated as it is by and large to souvenir programs of town fiestas and athletic meets, or to volumes commemorating the anniversaries of some city, town or province. It is, thus, that Philippine historiography is relatively poor in regional and municipal histories, and this, as might be imagined, leaves notable gaps in the knowledge of Philippine history which the more pretentious accounts are unable to fill. It is to help fill in this gap that this writer has embarked on the research and the writing of a history of the Ilocos. This paper, therefore, discusses the sources of the history of Ilocos.
Includes bibliographical references.